Metaphors We Think By: Conceptual Metaphors in the Architecture of Modern Ideologies (Liberalism, Marxism, Fascism) - Zainol Hasan; Risma Amin; Mirwan (Hikamatzu | Journal of Multidisciplinary, 2026)
This study offers a comparative cognitive-linguistic analysis of the conceptual metaphors that constitute the foundational architecture of three dominant modern ideologies: Liberalism, Marxism, and Fascism. Moving beyond traditional political theory, the research adopts the theoretical framework of Conceptual Metaphor Theory (Lakoff & Johnson, 1980) and Critical Metaphor Analysis (Charteris-Black, 2004) to argue that these ideologies are not merely systems of ideas but are fundamentally built from coherent, pre-conscious networks of metaphors that structure political reality, reasoning, and action. The methodology involves a systematic, three-phased analysis of canonical ideological texts: identification of linguistic metaphors, thematic synthesis into conceptual frameworks, and a comparative critical explanation. The findings reveal three distinct metaphorical architectures: (1) Liberalism is structured by mechanistic and market-based metaphors (e.g., society as a self-regulating machine, history as a linear journey of progress); (2) Marxism is built upon an architectural-geological-war triad (e.g., base/superstructure, class struggle as the engine of history); and (3) Fascism is centered on the organic-purification framework (e.g., the nation as a pure biological body requiring cleansing from pathogens). Crucially, the comparative analysis demonstrates that these systems are incommensurable; they employ shared source domains (e.g., BODY, JOURNEY, WAR) to construct mutually exclusive political ontologies, explaining the depth of ideological conflict. Furthermore, the study explicitly theorizes the critical link from metaphor to political praxis, showing how these cognitive models logically justify specific actions—from laissez-faire policy and revolutionary violence to genocidal purification. The study concludes that understanding modern political ideologies necessitates an examination of their deep metaphorical foundations. By making these constitutive architectures visible, the research provides a novel meta-understanding of political thought and underscores the critical importance of metaphorical literacy in political discourse. It contributes to transdisciplinary scholarship bridging cognitive science, linguistics, and political theory, highlighting how the metaphors we are compelled to think by ultimately shape the world we build and the actions we sanction.